PENGARUH KEWAJIBAN PENYEDIAAN MODAL MINIMUM, NON PERFORMING FINANCING DAN RETURN ON ASSETS TERHADAP PEMBIAYAAN PADA PERBANKAN SYARIAH (Studi Kasus pada Bank Umum Syariah) (Students' Journal of Accounting and Banking, 2014)
This study aims to examine and analyze the effect of capital adequacy ratio, net performing financing and return on assets for financing in Islamic banking. The population in this study are all listed Islamic bank in Indonesia Bank 2012-2013. Sampling technique is purposive sampling. Based on purposive sampling obtained a sample of as many as 8 companies with the amount of data that is processed as many as 64 observations. The data analysis technique used is multiple linear regression analysis. Based on the test results it can be concluded that the Capital Adequacy Ratio significant negative effect on financing. Non-Performing Financing negatively affect financing. Return on assets is not significant positive effect on the financing.Keywords: capital adequacy ratio, net performing financing, return on assets and financing